Eksplorasi Gerak Aktif: Mengembangkan Kepercayaan Diri dan Ketangkasan Fisik Anak melalui Fun Agility Game - Abriadi Abriadi; Juhanis Juhanis; Hasmawaty Hasmawaty; Muslim Muslim; Usman Usman (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
Motor development in early childhood is a crucial foundation for executive functions and psychosocial health. However, the current sedentary lifestyle and gadget dependency hinder the optimization of this physical potential. This community service aims to enhance children's self-confidence and physical agility through the "Active Movement Exploration: Fun Agility Game" program. The activity was conducted at TK Negeri PAUD Tamalate, Makassar, involving 93 children in the initial observation. The method employed was Guided Modeling-Practice, which includes agility circuit preparation, demonstration, and guided exploration. The game instruments included Zig-Zag Safari, Stop-Go Traffic, Balance River Stones, Ball-to-Target Trail, and Choose-Your-Path. The results showed a significant improvement in Fundamental Motor Skills (FMS), particularly in agility, balance, and manipulative coordination. Additionally, there was progress in psychological aspects, specifically in self-regulation, autonomy, and self-efficacy. In conclusion, the integration of structured yet enjoyable agility games is effective in building a strong physical and character foundation in early childhood.